Modeling of kinetics of macrochanneling of fast electrons and ions in planar gap collimators - Dyuldya, S.V.; Bratchenko, M.I.; Skorobogatov, M.A. (Вопросы атомной науки и техники, 2007)
Using the novel method of macroscopic computer simulation of the reflection of charged particles from solid surfaces at grazing incidence the kinetics of planar macrochanneling, the directed transport of particles between surfaces separated by macroscopic distance, has been studied for swift electrons and ions. The dechanneling functions at macrochanneling have been calculated for the first time. The modeling of angular distributions of particles has confirmed the effect of beam angular splitting at the exit of macrochannel. The method of the taking into account of surface atomic discreteness at modeling of coherent effects of ion planar semichanneling has been developed. It has been shown that due to stochastic effects of particles reflection the macrochanneling of electrons in long channels is actually reduced to the effects of beam collimation while for ions the coherent effect allows to stabilize the macrochanneling and to achieve the beam transportation at long distances without considerable losses of intensity. Оригінальним методом макроскопічного математичного моделювання відбиття заряджених частинок від поверхні твердого тіла досліджена кінетика площинного макроканалювання швидких електронів та іонів — орієнтованого транспорту частинок між поверхнями, розділеними макроскопічною відстанню. Вперше розраховані функції деканалювання частинок при макроканалюванні. Моделювання кутових розподілів підтвердило існування ефекту розділення потоків частинок. Розроблено метод урахування атомної дискретності поверхні в моделюванні когерентних ефектів площинного напівканалювання іонів. Показано, що з-за стохастичності процесу відбиття макроканалювання електронів в каналах великої довжини ефективно визначається механізмами колімації пучка, тоді як для іонів когерентний ефект дозволяє стабілізувати макроканалювання та досягти транспортування та розділення пучка на великих відстанях без значних втрат інтенсивності. Оригинальным методом макроскопического математического моделирования отражения заряженных частиц от поверхности твердого тела исследована кинетика плоскостного макроканалирования быстрых электронов и ионов — ориентированного транспорта частиц между поверхностями, разделенными макроскопическим расстоянием. Впервые рассчитаны функции деканалирования частиц при макроканалировании. Моделирование угловых распределений подтвердило существование эффекта разделения потоков частиц. Разработан метод учета атомной дискретности поверхности при моделировании когерентных эффектов плоскостного полуканалирования ионов. Показано, что ввиду стохастичности процесса отражения макроканалирование электронов в каналах большой длины эффективно определяется механизмами коллимации пучка, тогда как для ионов когерентный эффект позволяет стабилизировать макроканалирование и достичь транспортировки и разделения пучка на больших расстояниях без существенных потерь интенсивности.